Regulation of angiogenesis and choroidal neovascularization by members of microRNA-23∼27∼24 clusters - Zhou, Qinbo (National Academy of Sciences, 2011)
MicroRNAs (miRNAs) modulate complex physiological and pathological processes by repressing expression of multiple components of cellular regulatory networks. Here we demonstrate that miRNAs encoded by the miR-23∼27∼24 gene clusters are enriched in endothelial cells and highly vascularized tissues. Inhibition of miR-23 and miR-27 function by locked nucleic acid-modified anti-miRNAs represses angiogenesis in vitro and postnatal retinal vascular development in vivo. Moreover, miR-23 and miR-27 are required for pathological angiogenesis in a laser-induced choroidal neovascularization mouse model. MiR-23 and miR-27 enhance angiogenesis by promoting angiogenic signaling through targeting Sprouty2 and Sema6A proteins, which exert antiangiogenic activity. Manipulating miR-23/27 levels may have important therapeutic implications in neovascular age-related macular degeneration and other vascular disorders.